ANALISIS EFEKTIVITAS PENERAPAN PAJAK SARANG BURUNG WALET DI KABUPATEN MINAHASA - Lapian, Pingkan; Nangoi, Grace B.; Tangkuman, Steven J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Regional Income is derived from local taxes and levies. Local taxes in Indonesia based on Law No. 28 of 2009 is divided into two, namely, provincial taxes and tax districts / cities. Tax Swallow's Nest is a local tax. The aim of this study was to determine the effectiveness of taxation bird nest in Minahasa district. The analytical method used in this research is descriptive qualitative analysis to give you an idea whether the taxation of bird's nest has been effective or not and how much contribution it provides to the local revenue. The results showed that in 2011 the tax effectiveness of bird's nest of 22.28%, in 2012 amounted to 109.63%, in 2013 amounted to 129.48% and in 2014 amounted to 158.45% and the tax contributions of bird's nest on Revenue PAD in 2011 amounted to 0.09%, in 2012 amounted to 9.75%, in 2013 amounted to 8.12% and in 2014 amounted to 6.20%. It can be concluded taxation swallow nest in Minahasa district has been very effective and overall Contributions Tax swallow's nests against local revenue in 2011 through 2014 contributed greatly lacking.